Review of quantitative and functional lung imaging evidence of vaping-related lung injury - Hofmann, Joseph J.; Poulos, Victoria C.; Zhou, Jiahai; Sharma, Maksym; Parraga, Grace; McIntosh, Marrissa J. (Frontiers in Medicine, 2024)
Introduction The pulmonary effects of e-cigarette use (or vaping) became a healthcare concern in 2019, following the rapid increase of e-cigarette-related or vaping-associated lung injury (EVALI) in young people, which resulted in the critical care admission of thousands of teenagers and young adults. Pulmonary functional imaging is well-positioned to provide information about the acute and chronic effects of vaping. We generated a systematic review to retrieve relevant imaging studies that describe the acute and chronic imaging findings that underly vaping-related lung structure-function abnormalities. Methods A systematic review was undertaken on June 13th, 2023 using PubMed to search for published manuscripts using the following criteria: [(“Vaping” OR “e-cigarette” OR “EVALI”) AND (“MRI” OR “CT” OR “Imaging”)]. We included only studies involving human participants, vaping/e-cigarette use, and MRI, CT and/or PET. Results The search identified 445 manuscripts, of which 110 (668 unique participants) specifically mentioned MRI, PET or CT imaging in cases or retrospective case series of patients who vaped. This included 105 manuscripts specific to CT (626 participants), three manuscripts which mainly used MRI (23 participants), and two manuscripts which described PET findings (20 participants). Most studies were conducted in North America (n = 90), with the remaining studies conducted in Europe (n = 15), Asia (n = 4) and South America (n = 1). The vast majority of publications described case studies (n = 93) and a few described larger retrospective or prospective studies (n = 17). In e-cigarette users and patients with EVALI, key CT findings included ground-glass opacities, consolidations and subpleural sparing, MRI revealed abnormal ventilation, perfusion and ventilation/perfusion matching, while PET showed evidence of pulmonary inflammation. Discussion and conclusion Pulmonary structural and functional imaging abnormalities were common in patients with EVALI and in e-cigarette users with or without respiratory symptoms, which suggests that functional MRI may be helpful in the investigation of the pulmonary health effects associated with e-cigarette use.